Young men, poverty and aspirational masculinities in contemporary Nairobi, Kenya. Issue 12 (1st December 2020) - Izugbara, Chimaraoke O.; Egesa, Carolyne P.
Abstract: Building on recent calls for more focus on street-level optimism about life and the world, we address the question of 'aspirational masculinities' among poor urban young men in Kenya. Our data and material come from ethnographic work with young men in two slum communities in the country's capital city, Nairobi. While acknowledging that, in their neighborhoods, 'proper' masculinity is constituted in traditional terms of marriage, hardiness, provisioning, breadwinning and self-reliance, youth in our study aspired to masculinities characterized by 'abler' breadwinnerhood, caring, positive emotions, relationality, and the rejection of violence. The masculinity aspirations of poor Nairobi youth are complex; fashioned at the crossroads of structural constraints and agentive projects for a good life, and simultaneously supportive and resistive of traditional hegemonic manliness ideals. These aspirations are limited by and reflect an objective condition of everyday and enduring inequality while also signifying a deep unmet yearning for positive social and livelihood changes.